The chronicle of Ibn al-Athir for the Crusading period from al-Kamil fi'l-Ta'rikh. The years 541-589/1146-1193: the age of Nur al-Din and Saladin / Part 2, ([2020?]) - Ibn al-Athīr, ʿIzz al-Dīn, 1160-1233
No abstract available